Very human bears: Wild brown bear neo-taphonomic signature and its equifinality problems in archaeological contexts - Rosell, Jordi; Blasco, Ruth; Arilla, Maite; Fernández-Jalvo, Yolanda (Quaternary International, 2019)
Different agents can lead to similar damage patterns, and different causes can result in the same type of modification. This phenomenon was defined by Lyman (1987) as a problem of equifinality, with which the researcher warned about the risks of making direct systematic correlations. The fact that a specific type of damage cannot be linked to a single actor, behaviour or ecological context is primarily applicable to damage associated with the direct consumption of carcasses. Some carnivores show physical and dental characteristics that could lead to bone modifications potentially like those generated by humans. For example, bears have a bunodont dentition and plantigrade locomotion –the latter allows them to frequently release and use their claws as “hands”. Here, we present the neo-taphonomical study of 17 ungulate carcasses eaten by wild brown bears (Ursus arctos arctos) in the Spanish Pyrenees. Our observations express this equifinal problem due to the similarities between tooth marks and peeling generated by both bears and humans. This fact is especially significant, given that peeling and the combination of this damage with visible tooth marks were primarily associated with the feeding activities of humans and chimpanzees (Pan troglodytes) and only anecdotally with other taphonomic agents, such as spotted hyenas. With this research, we try to show some equifinal phenomena that could occur in Pleistocene faunal assemblages as well, where the presence of both hominids and bears is documented. This study is part of the Spanish MINECO/FEDER projects CGL2015-65387-C3-1-P (JR), CGL2016-80000-P (JR) and CGL2015-68604-P (RB), the Generalitat de Catalunya-AGAUR projects 2017 SGR 836 and CLT009/18/00055 (JR, RB, MA). MA is the beneficiary of a research fellowship (FI) from AGAUR (2017FI-B-00096).